Social Media Use and Anxiety Levels Among Nursing Students in Indonesia: A Cross-Sectional Study - Riyanto, Dwi Agung; Musfirowati, Fifi; Ernawati, Ernawati; Sumartini, Rina; Mulyati, Mulyati; Chairulfalah, Achmad Machron (Chakra Brahmanda Lentera Institute, 2026)
Background: The widespread use of social media among students is associated with increased anxiety levels. In Indonesia, high social media use combined with limited institutional support may heighten students’ vulnerability. Although some studies report benefits such as social support and stress relief, evidence suggests negative impacts are more common. Therefore, this study examines the relationship between social media use and anxiety among nursing students. Methods: This study used a cross-sectional correlational design. A purposive sampling method was applied to select active students who use social media for at least three hours per day and were willing to participate, resulting in 57 respondents. Data were collected through an online questionnaire covering social media usage duration, platform types, and content types. Anxiety levels were measured using the validated Generalized Anxiety Disorder-7 (GAD-7) instrument and categorized into low (≤9) and high (≥10) anxiety. Data were analyzed using the Chi-Square test with Odds Ratios (OR) and 95% Confidence Intervals (CI) at a significance level of p < 0.05. Results: A significant relationship was found between social media usage duration and anxiety levels (p = 0.022). Students who utilized social media for less than three hours per day had a lower likelihood of experiencing high anxiety (OR = 0.254; 95% CI: 0.08–0.79). The type of platform was also significantly associated with anxiety (p = 0.038), where Instagram and WhatsApp users exhibited a greater proportion of high anxiety compared to TikTok users. Content type further demonstrated a meaningful relationship (p = 0.032); educational content was associated with a higher proportion of low anxiety compared to entertainment and informational content Conclusion: The use of social media among nursing students is related to anxiety dynamics influenced by usage duration, platform characteristics, and content types. These findings underscore the importance of a promotive approach based on digital capabilities and anxiety level screening within higher education settings to support students' psychological well-being.